Eating in the absence of hunger in children with mild sleep loss: a randomized crossover trial with learning effects. Issue 4 (30th June 2021) - Morrison, Silke; Galland, Barbara C; Haszard, Jillian J; Jackson, Rosie; McIntosh, Deborah R; Beebe, Dean W; Elder, Dawn E; Ward, Aimee L; Meredith-Jones, Kim; Taylor, Rachael W
ABSTRACT: Background: While insufficient sleep duration has emerged as a strong, independent risk factor for obesity, the mechanisms remain unclear. One possibility is greater "eating in the absence of hunger" (EAH) or energy intake beyond the point of satiety, when tired. Objective: The aim was to determine whether mild sleep loss increases EAH in children. Methods: A crossover study was undertaken in 105 healthy children (8–12 y) with normal sleep (∼8–11 h/night). After randomization, children went to bed 1 h earlier (sleep extension) or 1 h later (sleep restriction) than their usual bedtime, over 2 intervention weeks separated by a 1-wk washout. At the end of each intervention week, children underwent an EAH feeding experiment involving a preloading meal until satiation, followed by an ad libitum buffet (of highly palatable snacks) to measure EAH, with each food item weighed before and after consumption. Results: Ninety-three children completed the EAH experiment. There was no evidence of a difference in energy intake from EAH between sleep restriction and extension conditions when analyzed as a crossover design. However, a learning effect was found, with children eating significantly less (−239 kJ; 95% CI: −437, −41 kJ; P = 0.018) during the preload phase and significantly more (181 kJ; 95% CI: 38, 322 kJ; P = 0.013) in the ad libitum phase in the second week. No significant differences were seen using an underpowered parallel analysis for energy intake during the ad libitum phase when sleep deprived (106 kJ; 95% CI: −217, 431 kJ; P = 0.514). Conclusions: Our findings suggest that measuring a difference in eating behavior in relation to sleep proved unsuitable using the EAH experiment in a crossover design in children, due to a learning effect. This trial was registered at the Australian New Zealand Clinical Trials Registry (http://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=367587&isReview=true ) as ACTRN12618001671257 .